Vocational Orientation of Primary School Students by Teaching Vocational Vocabulary - Saipova Hilola Abdulhamitovna; Ahmadaliyeva Maftuna Sodiqovna (Zien Journals, 2023)
This article analyzes the process of guiding primary school students to the profession by teaching them vocational lexicon. also given about personality traits, student psychology, criteria indicating students' readiness to choose a profession, content of age stages of preparing students for choosing a profession. Methodological recommendations have been developed on the topic.
Keywords: teacher; student; primary education; profession